2016
DOI: 10.1016/j.ocemod.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Ocean surface waves in Hurricane Ike (2008) and Superstorm Sandy (2012): Coupled model predictions and observations

Abstract: Forecasting hurricane impacts of extreme winds and flooding requires accurate prediction of hurricane structure and storm-induced ocean surface waves days in advance. The waves are complex, especially near landfall when the hurricane winds and water depth varies significantly and the surface waves refract, shoal and dissipate. In this study, we examine the spatial structure, magnitude, and directional spectrum of hurricane-induced ocean waves using a high resolution, fully coupled atmosphere-wave-ocean model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 24 publications
0
66
0
Order By: Relevance
“…We use highly realistic winds and waves from a coupled ocean‐atmosphere‐wave model to implement the parameterization for V cor and V W . The source for the synoptic wind and wave data used in this study is the UWIN‐CM (Chen & Curcic, ; Chen et al, ). It is designed as a multimodel system with the flexibility of exchanging individual model components for the atmosphere, waves, ocean, land, and sea ice.…”
Section: Methodsmentioning
confidence: 99%
“…We use highly realistic winds and waves from a coupled ocean‐atmosphere‐wave model to implement the parameterization for V cor and V W . The source for the synoptic wind and wave data used in this study is the UWIN‐CM (Chen & Curcic, ; Chen et al, ). It is designed as a multimodel system with the flexibility of exchanging individual model components for the atmosphere, waves, ocean, land, and sea ice.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advancement in high‐resolution, fully coupled atmosphere‐wave‐ocean modeling made it possible to study the hurricane‐induced surface waves and Stokes drift. Chen and Curcic [] showed that the coupled model predictions of ocean surface waves in Hurricane Ike (2008) and Superstorm Sandy (2012) were verified very well against both in situ observations from the National Data Buoy Center buoys and the satellite observations. The coupled modeling studies by Chen et al [] and Chen and Curcic [] have shown that hurricane‐induced surface waves are highly complex and asymmetric in terms of wave heights and propagation directions around a moving storm.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, passive OGCM simulations where wind forcing is not affected by the ocean states should be improved to a coupled atmosphere-wave-ocean model to better simulate the dynamics across the atmosphere-ocean interface. Based on the insight provided by the present experiences, work is underway to enhance both the construction and propagation of more realistic uncertain input fields, particularly by relying on the fully coupled atmospherewave-ocean model [6]. Results from this ongoing effort will be reported in a future study.…”
Section: Resultsmentioning
confidence: 98%
“…However, due to the rapid increase in the basis size when increasing the polynomial order, the hyperbolic truncation introduced in [40] is employed in this study. Specifically, we use an isotropic polynomial basis which is the union set of three hyperbolic truncated basis given by maximum total order of No = [6,20,35]; the corresponding truncation parameters are q = [1, 0.55, 0.42], respectively. The choice of this basis has been carefully analyzed for all the approximations constructed below.…”
Section: Polynomial Chaos Approximationmentioning
confidence: 99%